Curbing the menace of antimicrobial resistance in developing countries. - Nweneka, Chidi Victor.; Tapha-Sosseh, Ndey.; Sosa, Anibal. (2016)
Abstract: Several reports suggest that antimicrobial resistance is an increasing global problem; but like most pandemics, the greatest toll is in the less developed countries. The dismally low rate of discovery of antimicrobials compared to the rate of development of antimicrobial resistance places humanity on a very dangerous precipice. Since antimicrobial resistance is part of an organism's natural survival instinct, total eradication might be unachievable; however, it can be reduced to a level that it no longer poses a threat to humanity. While inappropriate antimicrobial consumption contributes to the development of antimicrobial resistance, other complex political, social, economic and biomedical factors are equally important. Tackling the menace therefore should go beyond the conventional sensitization of members of the public and occasional press releases to include a multi-sectoral intervention involving the formation of various alliances and partnerships. Involving civil society organisations like the media could greatly enhance the success of the interventions; Keywords: antimicrobial resistance, Alliance for the Prudent Use of Antibiotics, civil society organisations, health care workers, methicillin resistant staphylococcal aureus, United Kingdom.; Springer Open.